Prevalence of malnutrition and associated factors among older adults from urban and rural residences of Metu district, Southwest Ethiopia - Yohannes Mulu Ferede; Terefe Derso; Mekonnen Sisay (BMC Nutrition, 2022)
Abstract Background In Ethiopia, the proportion of older adults is steadily increasing. This rapidly growing older adult population may increase the burden of malnutrition. However, malnutrition among older adults, particularly those living in rural areas, is regularly underrecognized and/or ignored. There have been no studies among older adults in the Metu district that have used the Min nutritional assessment (MNA). As a result, the purpose of this study is to determine the prevalence of malnutrition and its associated factors among older adults in Metu district, Southwest Ethiopia. Methods A community-based comparative cross-sectional study was conducted from May to June 2021 in Metu district. A multi-stage stratified sampling technique was employed. The nutritional status of the older adults was measured by MNA. Data from 616 older adults (308 from urban and 308 from rural residences) was collected through face-to-face interviews using a structured questionnaire. Bivariable and multivariable logistic regression analyses were done to identify factors associated with malnutrition. Results According to this study, the overall prevalence of malnutrition in Metu district was 17.5% (95% CI: 14.4%–20.7%). The prevalence of malnutrition in urban and rural residences was 9.9% and 25.2%, respectively. In the overall study, insomnia (AOR: 2.0, 95%CI: 1.1–3.7), residence (AOR: 3.47, 95%CI: 1.8–6.5), and smoking (AOR: 3.7, 95%CI: 2.1–6.7) were associated with malnutrition. In urban residences, depression (AOR: 3.4, 95%CI: 1.2–9.5), dietary diversity score (DDS) (AOR: 3.5, 95%CI: 1.2–10.0), and eating problems (AOR: 2.8, 95%CI: 1.1–7.3) were associated with malnutrition. In rural residence, age (AOR:3.8; 95%CI: 1.2–11), sex (AOR:2.2,95%CI:1.0–4.8), DDS (AOR:5.4,95%CI:2.2–13.3), depression (AOR: 4.6,95%CI:2.2–9.2), and chronic disease (AOR: 3.8 95%CI: 1.8–8.2) were associated with malnutrition. Conclusions and recommendations Malnutrition was more prevalent among older adults living in rural areas than in urban areas. In the overall study, insomnia, residence, and smoking were significantly associated with malnutrition. DDS, depression, and eating difficulties were significantly associated with malnutrition among older adults living in urban areas, whereas sex, age, depression, chronic disease, and dietary diversity were factors influencing malnutrition in rural areas. Strengthening strategies aimed at addressing nutrition policy, as well as paying attention to the nutritional needs of the older adult population, can help to improve the health and quality of life of older adults.